Studying the Effect of Curcumin (Standard & Supplements) and Zinc on the Concentrations of Glucose, Insulin, HOMA-IR, and Anti-Mullerian Hormone in PCOS-Model Rats - Suaad Muhammed Abd-Alqader; Sameerah Ahmed Zearah; Iqbal J. Al-Assadi (مجلة بغداد للعلوم)
The goal of the current study was to investigate the effects of curcumin in both formulas (supplement and standard), zinc, and then use them together to show their effect on the levels of glucose, insulin, insulin resistance (IR), and anti-mullerian hormone (AMH) in the model of female rats with induced polycystic ovary syndrome (PCOS) using 1mg/kg/day of letrozole for 21 days followed by a treatment period of 14 days including different treatments of zinc 30 mg/kg, curcumin standard 200 mg/kg, curcumin supplement 200 mg/kg, (curcumin standard plus zinc), (curcumin Supplement plus zinc) and metformin as a standard treatment. After the treatment, all female rats were sacrificed, and blood samples were collected from the inferior vena cava of each rat for biochemical measurements. The concentrations of insulin and AMH were measured by using of immunoassay technique ELISA. Glucose was determined by using the spectrophotometric method while insulin resistance is measured by calculation methods. The results indicate that the administration of letrozole as an aromatase inhibitor resulted in a significant elevation of anti-mullerian hormone (AMH), glucose, insulin, and insulin resistance in the polycystic ovary syndrome-designed model. Curcumin (standard or supplement) and zinc showed a significant decrease in insulin levels in all treatment groups, while the effect was more pronounced when zinc was taken with a curcumin supplement. Results also showed a significant decrease in glucose and IR, this indicates the ability of curcumin supplement and zinc to restore glucose and IR to their normal level in the healthy control group. Anti–mullerian hormone decreased significantly for all groups that took both forms of curcumin, and curcumin and zinc together, while the decrease was highly significant in curcumin supplement and zinc